Phenolic-rich extract of Nopalea cochenillifera attenuates gastric lesions induced in experimental models through inhibiting oxidative stress, modulating inflammatory markers and a cytoprotective effect. Issue 7 (17th March 2023) - da Silva, Elaine Cristine Souza; Bernardo Guerra, Gerlane Coelho; de Araújo, Edilane Rodrigues Dantas; Schlamb, Jade; da Silva, Valéria Costa; de Aragão Tavares, Emanuella; Dantas-Medeiros, Renato; Abreu, Lucas Silva; Fechine Tavares, Josean; de Araújo Júnior, Raimundo Fernandes; Esposito, Debora; Moncada, Marvin; et al.
Abstract : Nopalea cochenillifera (Cactaceae), popularly known as "palma" or "palma doce", is from Mexico, but it was widely introduced in Brazil through crops. Abstract : Nopalea cochenillifera (Cactaceae), popularly known as "palma" or "palma doce", is from Mexico, but it was widely introduced in Brazil through crops. It has been used as food and in traditional medicine and is a good source of phenolic compounds. In this study the phytochemical profile and gastroprotective activity of phenolic-rich extract of N. cochenillifera in acute gastric lesion models induced by ethanol and indomethacin were evaluated. High-performance liquid chromatography coupled with mass spectrometry (HPLC/ESI/MS n ) allowed the characterization of 12 compounds such as sugars, phenolics and flavonoids. Among polyphenols, the main peak was assigned to isorhamnetin-3- O -(2′′, 3′′- O -di-rhamnose)-glucoside. The TPC and TFC in the dry extract were 67.85 mg of gallic acid equivalent per g/extract and 46.16 mg quercetin equivalent per g/extract, respectively. In the in vitro MTT assay, the extract showed no cytotoxicity and suppressed ROS levels in LPS-treated RAW 264.7 cells. Preclinical models in rats showed that a dose of 100 mg kg −1 ( p < 0.0001) in the ethanol model and doses of 100 mg kg −1 ( p < 0.5) and 200 mg kg −1 ( p < 0.01) in the indomethacin model reduced the gastric lesions. Also, the extract reduced the MPO, MDA, TNF-α and IL-1β levels and increased the GSH and IL-10 levels. The pre-treatment with the extract led to the upregulation of SOD and the downregulation of COX-2 by immunohistochemical analysis. It also showed a cytoprotective effect in the histopathological analysis and stimulated the restoration of the mucus content as observed in the periodic acid–Schiff analysis without modifying the pH, volume or total acidity of the gastric juice. Taken together, N. cochenillifera extract can be applied as a novel gastroprotective ingredient for food or pharmaceutical products.